2017
DOI: 10.1515/tjeb-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Performance Perspectives for Small and Medium Enterprises in Cameroon: Innovation and ICTs

Abstract: This paper studies the combined effects of innovation and information and communication technologies (ICT) on the performance of Small and Medium Enterprises (SMEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In addition, there is a significant relationship between business information strategy and performance of women-owned SMEs in Southwestern, Nigeria. This supports the findings of Pires and Aisbett (2003), Organisation for Economic Co-Operation and Development (OECDs) (2004), Tsambou and Kamga (2014), and Govender and Pretorius (2015) that business information strategy does enhance SMEs' performance. Also, the findings buttressed the work of Sandada et al (2014) that business information strategy affects SMEs' performance.…”
Section: Discussion Of Findingssupporting
confidence: 84%
See 4 more Smart Citations
“…In addition, there is a significant relationship between business information strategy and performance of women-owned SMEs in Southwestern, Nigeria. This supports the findings of Pires and Aisbett (2003), Organisation for Economic Co-Operation and Development (OECDs) (2004), Tsambou and Kamga (2014), and Govender and Pretorius (2015) that business information strategy does enhance SMEs' performance. Also, the findings buttressed the work of Sandada et al (2014) that business information strategy affects SMEs' performance.…”
Section: Discussion Of Findingssupporting
confidence: 84%
“…The findings of this study revealed that ICT adoption does not have significant relationship with performance of women-owned SME in Nigeria. This contrast the works of Croteau and Bergeron (2001), Hoque (2015), Laudon et al (2006), Ashrafi and Murtaza (2008), Ajiferuke and Olatokun (2009), Jamil and Mohamed (2011), Sajuyigbe and Alabi (2012), Janke and Packová (2013), Ladokun et al (2013), Tarutė and Gatautis (2014), Tsambou and Kamga (2014), Ifijeh et al (2015), Mesároš et al (2016), and Omiunu (2017) that ICTs can improve the quality and performance of SMEs. The findings of this study support the work of Ajiferuke and Olatokun (2009) that Nigeria, like most developing countries, is an "information-poor" country where the adoption and use of ICTs is still in its infancy, thus affecting performance of SMEs in Nigeria, and differs work of and Ladokun et al (2013) that SMEs in Nigeria are not familiar with the use of various ICTs in a way that could enhance their performance.…”
Section: Discussion Of Findingsmentioning
confidence: 88%
See 3 more Smart Citations